Philosophical Basis of Various Polygynous Requirements: Comparative Study of Family Law’s Philosophy in Asia and Africa - Lia Noviana; Asep Awaludin (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2022)
Polygyny is one of the objects to reform Islamic family law in modern Muslim countries. In addition to meeting the demands of the times, the renewal of polygyny regulations also aims to improve the position and protect women's rights. Most modern Muslim countries have renewed polygyny regulations by limiting and prohibiting polygyny accompanied by criminalization. This study utilizes a comparative descriptive method to compare the polygynous requirements in Indonesia, Morocco, Tunisia, Somalia, Turkey, and Pakistan from the perspective of the philosophy of Islamic law. The research findings show that the categorization of polygyny regulations in modern Muslim countries consists of: absolute prohibition of polygyny, permissibility with strict conditions, permissibility with weak conditions, obligation to seek court permission, and criminalization of polygyny. There are two main elements required for polygyny in modern Muslim countries: an internal element in the form of the condition of husband and wife and an external component in the form of the role of the court institution in granting polygyny permits. Thus, the philosophical basis of these differences is mostly caused by the diversity of Madhabs in each country that aimed to maintain their people’s prosperity and to renew Islamic family law which brings a contemporary spirit especially the embodiment of equality and increase in the position of women